Psychological Resilience and Its Relationship with Some 21st Century Skills Among Students of the Education Department at the University of Nizwa - Almazidi, Nasser Sulaiyam; Alobaidania, Khulood Ahmed (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to explore the levels of psychological resilience, critical thinking skills, problem-solving skills, and digital skills among education students at the University of Nizwa in the Sultanate of Oman. The study also aimed to reveal the relationship between psychological resilience and critical thinking skills, problem-solving skills, and digital skills. A descriptive approach was used to achieve the study objectives. The study sample consisted of (260) male and female education students in the spring semester of the 2024/2025 academic year. To collect the study data, the researchers constructed a scale consisting of four variables. The study results showed that the levels of psychological resilience, critical thinking skills, problem-solving skills, and digital skills were high. The results also revealed a strong positive correlation between the study variables. Considering the study results, it was recommended that specialized workshops be held on psychological resilience and some 21st century skills for in-service teachers.